Experiences with a PDA-based documentation system in clinical research - Becker, Torben Kim; Martin, Eike (Journal of medical systems, 2012)
New clinical treatment concepts and the implementation of algorithms usually require extensive documentation for scientifical evaluation and quality assurance. A consequent electronic documentation approach potentially facilitates data integrity and availablity and decreases the amount of time spent with manual transfer from paper data into computer systems. The development and the components of the “Heidelberg PDA-based Clinical Documentation Suite” are described. This system allows electronic documentation and post-processing in a timely manner using an affordable standard Personal Digital Assistant (PDA). It features almost universal customizability to new documentation requirements and can be used with only minimal prior training. Initial experiences are reported and prospective improvement possibilities are discussed.